Variabel yang Mempengaruhi Keberhasilan Usaha di Pasar Pramuka Jakarta Timur - Nur Wahyuni; Friswi Novati; Farida Farida (IKRAITH-EKONOMIKA, 2023)
This study aims to determine the effect of price, product quality and location on business success in the Pramuka Market, East Jakarta. The method used in this study is a quantitative method. In this method data collection uses a questionnaire technique and is distributed to all business actors. In statistical analysis the author uses the SPSS (Statistical Package For The Social Science) version 25.0 for windows. From the data management carried out with the SPSS (Statistical Package For The Social Science) version 25.0 program with a sample of 77 respondents. Then the R Square (determination) is 0.606 or 60.6% and the remaining 39.8% is the contribution of other variabels. For multiple regression values, = 1.358 + 0.369X1 + 0.233X2 + 0.392X3 and the F test with = 5% is obtained by the Fcount value of 39.896 and Ftable of 3.12 meaning Fcount > Ftable, then H0 is rejected and Ha is accepted. This shows that Price, Product Quality and Location have a joint effect on Business Success.